1988
DOI: 10.1002/art.1780311002
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous synthetic phenotype of cloned scleroderma fibroblasts may be due to aberrant regulation in the synthesis of connective tissues

Abstract: Clones of dermal fibroblasts from the skin of 4 normal subjects and 5 patients with progressive systemic sclerosis (PSS; scleroderma) were established, and their synthetic and proliferative characteristics were compared. A limiting‐dilution assay was used to determine frequencies of cloning in the microcultures of dermal fibroblasts plated. The clones derived from single cells were expanded in vitro and examined (in passages C–H) for growth and synthesis of glycosaminoglycan (GAG) and collagenase‐sensitive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…From lung tissue, for example, fibroblasts have been shown to be heterogeneous with regard to morphology (15,34), proliferative capacity (6,20,24,34,48), surface marker (Thy-1, MHC class II, CD4) expression (11,34), type and amount of collagen production (11,16), intracellular metabolic pathways (15), and cytokine production (15). In addition, fibroblasts from nonpulmonary tissues have been shown to be heterogeneous with regard to proliferation (2,22), size and shape (18,19), presence of lipid droplets (29), collagen synthesis (13,16,21,36,40,49,51), expression of growth factors (16), response to and synthesis of PGE 2 , and expression of C1q surface receptors, among others. One wonders about heterogeneity in some of the other key functions of fibroblasts, such as capacity for transition to other cell types (i.e., myofibroblast and/or SM cell), migration, protease expression, and propensity to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…From lung tissue, for example, fibroblasts have been shown to be heterogeneous with regard to morphology (15,34), proliferative capacity (6,20,24,34,48), surface marker (Thy-1, MHC class II, CD4) expression (11,34), type and amount of collagen production (11,16), intracellular metabolic pathways (15), and cytokine production (15). In addition, fibroblasts from nonpulmonary tissues have been shown to be heterogeneous with regard to proliferation (2,22), size and shape (18,19), presence of lipid droplets (29), collagen synthesis (13,16,21,36,40,49,51), expression of growth factors (16), response to and synthesis of PGE 2 , and expression of C1q surface receptors, among others. One wonders about heterogeneity in some of the other key functions of fibroblasts, such as capacity for transition to other cell types (i.e., myofibroblast and/or SM cell), migration, protease expression, and propensity to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The ease with which fibroblasts proliferate from either tissue explants or established cultures stands in sharp contrast with the difficulty encountered when growing them from single cells. A number of investigators have shown that single dermal fibroblasts, as obtained through dilutional techniques, fail to proliferate in spite of optimal culture conditions (Korn et al, 1984;Whiteside et al, 1988). In this report, we tested the hypothesis that low oxygen tension, which has been shown to stimulate the proliferation and lifespan of fibroblasts (Taylor et al, 1974;Packer and Fuehr, 1977;Balin et al, 19841, would initiate and maintain their proliferation starting from single cells.…”
mentioning
confidence: 89%
“…Although the pathogenesis of SSc is still unknown, it is obvious that skin fibrosis results from excessive accumulation of extracellular matrix (2) and that skin fibroblasts from patients with SSc express more collagen mRNA and protein than do normal skin fibroblasts in vivo and in vitro (3)(4)(5). A number of researchers have examined the mechanisms of the abnormal functions of SSc fibroblasts (6)(7)(8)(9)(10), but many facets of the pathogenesis of SSc remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%